2017
DOI: 10.1080/24750573.2017.1338822
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte and platelet/lymphocyte ratios in all mood states of bipolar disorder

Abstract: Objectives: This study aims at researching the inflammatory cells and their ratios as inflammation markers in different phases of patients with bipolar disorder (BD). Methods: In this retrospective study, 79 manic, 61 depressed, 59 euthymic drug-naive patients with BD, and 86 control subjects have been evaluated for their complete blood count. Results: Neutrophil/lymphocyte ratio (NLR) was found to be significantly higher in manic, euthymic, and depressed patients with BD compared to control group. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…NLR, PLR and MLR have been studied in psychiatric disorders, including MDD and BD [24]. Numerous studies have established NLR and PLR as biomarkers for the manic phase of bipolar disorder [29][30][31][32][33][34][35]. These results have been confirmed by a meta-analysis conducted by Mazza et al (2018).…”
Section: Introductionmentioning
confidence: 80%
“…NLR, PLR and MLR have been studied in psychiatric disorders, including MDD and BD [24]. Numerous studies have established NLR and PLR as biomarkers for the manic phase of bipolar disorder [29][30][31][32][33][34][35]. These results have been confirmed by a meta-analysis conducted by Mazza et al (2018).…”
Section: Introductionmentioning
confidence: 80%
“…In a study on platelet and MPV levels in ADHD, MPV found to be higher than controls, but no difference found in platelet levels (22). There are some studies which indicate NLR as an inflammatory marker can increase in depression, bipolar disorder and schizophrenia (19,(23)(24)(25)(26). PLR is a sensitive inflammatory marker and prognostic factor in some malignancies (27).…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been repetitively tested as a candidate parameter for systemic inflammation in neuropsychiatric disorders such as Alzheimer's disease [13] and schizophrenia [14,15]. A few studies also attempted to examine peripheral inflammatory response in mood disorders by means of NLR and/or PLR, with their findings collectively suggesting that MDD [16], as well as different mood episodes of BD [17] are associated with increased NLR and/or PLR compared to HC. On the other hand, some other studies addressing the relationship between clinical severity of MDD and NLR-PLR provided rather inconsistent findings [18,19].…”
Section: Original Articlementioning
confidence: 99%